2021
DOI: 10.1016/j.ijscr.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Colon perforation caused by transanal decompression tube after laparoscopic low anterior resection: A case report

Abstract: Highlights The effectiveness of a transanal decompression tube to prevent anastomotic leakage after rectal surgery is widely accepted. A rare complication of colonic perforation due to a transanal decompression tube may occurred. The relationship between the tip of the transanal decompression tube, the intestine and the sacrum might be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Additionally, Hiraki et al reported perforation of the anterior wall of the proximal colon due to TDT placement. These authors demonstrated that looseness of the remaining oral intestinal tract depressed in the pelvis might compress the colon by the TDT 4 . Thus, looseness of the remaining oral intestinal tract can cause instability of the tip of the TDT and perforation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Hiraki et al reported perforation of the anterior wall of the proximal colon due to TDT placement. These authors demonstrated that looseness of the remaining oral intestinal tract depressed in the pelvis might compress the colon by the TDT 4 . Thus, looseness of the remaining oral intestinal tract can cause instability of the tip of the TDT and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors demonstrated that looseness of the remaining oral intestinal tract depressed in the pelvis might compress the colon by the TDT. 4 Thus, looseness of the remaining oral intestinal tract can cause instability of the tip of the TDT and perforation. Although this is a hypothesis, the correct position of the tip of the TDT may pass over the promontorium and place the tube as proximal as possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations